A method and system for predicting resource utilization of shield slag

By conducting dry and wet cycle testing and data detection of shield soil, a comprehensive evaluation system was established, and the systematic problem of research on the resource utilization of shield soil was solved, and efficient utilization of shield soil resources and environmental sustainable development were achieved. .

CN119151077BActive Publication Date: 2025-02-18EAST CHINA JIAOTONG UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411621086.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-18
Estimated Expiration
2044-11-14

AI Technical Summary

Technical Problem

The existing technology has not yet conducted systematic research and comprehensive evaluation of the mechanical properties, physical mechanisms, shrinkage properties of shield slag materials, which limits the analysis and mining of their resource utilization.

Method used

Based on the material characteristics of shield slag, a sample is selected, and a resource prediction experimental plan is formulated, including dry and wet cycle testing and data detection, a comprehensive evaluation system is established, and a multi-dimensional evaluation of the resource utilization potential of shield slag.

Benefits of technology

Through multi-dimensional evaluation, we will deeply analyze the feasibility of resource utilization of shield soil, provide a theoretical and practical basis for resource utilization research, and achieve maximum resource utilization and sustainable environmental development.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119151077B_ABST
    Figure CN119151077B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of resource recycling, specifically to a method and system for predicting the resource utilization of shield slag, the method for predicting the resource utilization of shield slag comprising: selecting a shield slag sample, formulating a resource prediction experimental plan for the shield slag based on the shield slag sample; obtaining experimental information on resource utilization of the shield slag sample based on the resource prediction experimental plan and the shield slag sample; establishing a shield slag resource utilization evaluation system based on the resource utilization experimental information, obtaining a multi-dimensional evaluation result of resource utilization of the shield slag sample based on the resource utilization evaluation system and the resource utilization experimental information; and comprehensively predicting the resource utilization degree of the shield slag sample in combination with the multi-dimensional evaluation result of resource utilization and the resource utilization experimental information. The resource utilization evaluation system of the present invention can comprehensively reflect the resource utilization effect of shield slag, and is helpful to promote the resource utilization and sustainable development of shield slag.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of resource recycling, and in particular to a method and system for predicting resource utilization of shield slag. Background Art

[0002] Although certain research results have been achieved in shield tunnel wall grouting materials at home and abroad, there is still a certain research gap in the resource utilization technology of solid waste such as shield slag as the main raw materials. At present, there has been no systematic research and comprehensive evaluation of the mechanical properties, physical mechanism, shrinkage properties and other key properties of shield slag materials, which has limited the material research and development of shield slag and the analysis and exploration of resource utilization.

[0003] Now it is necessary to effectively analyze and predict the resource utilization degree of shield slag, reveal the various properties of shield slag materials and their influencing factors, provide new ideas and references for the research and development of shield slag materials, and further promote the resource utilization of solid waste such as shield slag. Therefore, it is necessary to strengthen the research and evaluation of the resource utilization of shield slag and further promote related technological progress and industrial upgrading. Summary of the invention

[0004] In view of the shortcomings of existing methods and the needs of practical applications, in order to comprehensively and systematically explore the performance and changing laws of shield slag materials in multiple dimensions such as physical properties, mechanical properties and durability, the present invention constructs a comprehensive evaluation system based on slag information, and conducts a multi-dimensional evaluation of the resource utilization potential of shield slag samples, which helps to deeply analyze the feasibility of resource utilization of shield slag, further provide a theoretical and practical basis for resource utilization research, and help to achieve maximum resource utilization and sustainable environmental development. On the one hand, the present invention provides a method for predicting the resource utilization of shield slag, and the method includes: selecting a shield slag sample, formulating a resource prediction experimental plan for the shield slag based on the shield slag sample; obtaining experimental information on resource utilization of the shield slag sample based on the resource prediction experimental plan and the shield slag sample; establishing a shield slag resource utilization evaluation system based on the resource utilization experimental information, and obtaining a multi-dimensional evaluation result of resource utilization of the shield slag sample based on the shield slag resource utilization evaluation system and the resource utilization experimental information; and comprehensively predicting the resource utilization degree of the shield slag sample in combination with the multi-dimensional evaluation result of resource utilization and the resource utilization experimental information. The present invention selects representative shield slag samples, and can obtain key performance parameters of shield slag in the resource utilization process, which is helpful to comprehensively and accurately evaluate the resource utilization degree of shield slag, further promote the resource utilization of shield slag, and realize the sustainable development of shield slag materials.

[0005] Optionally, the selecting of shield slag samples and formulating a resource prediction experimental scheme for shield slag based on the shield slag samples include: selecting shield slag samples based on the material characteristics of the shield slag, the shield slag samples include multiple groups of shield slag samples with different components; formulating a resource prediction experimental scheme for shield slag based on the shield slag samples, the resource prediction experimental scheme including dry-wet cycle testing and shield slag data detection. The present invention can ensure the representativeness and extensiveness of the experimental results by selecting samples based on the material characteristics of the shield slag, not only to understand the actual performance of the shield slag, but also to compare and analyze the effects of slag with different components on the resource utilization effect, and provide more comprehensive reference information for subsequent resource utilization.

[0006] Optionally, the resource utilization experimental information of the shield slag sample obtained according to the resource prediction experimental plan and the shield slag sample includes: performing the dry-wet cycle test on the shield slag sample to obtain the shield slag sample after the dry-wet cycle test; performing shield slag data detection on the shield slag sample after the dry-wet cycle test to obtain the resource utilization experimental information of the shield slag sample. The present invention performs dry-wet cycle test on the shield slag sample, and the behavior characteristics of the shield slag under different humidity conditions, such as expansion, contraction, strength change, etc., can be observed, which is helpful to more comprehensively evaluate the relevant performance of the shield slag in the resource utilization process.

[0007] Optionally, the establishment of a shield slag resource utilization evaluation system based on the resource utilization experimental information includes: setting resource utilization evaluation indicators according to the resource utilization experimental information, the resource utilization evaluation indicators including the physical phase composition indicators, mechanical property indicators and shrinkage change indicators of the shield slag sample; the physical phase composition indicators, the mechanical property indicators and the shrinkage change indicators constitute the shield slag resource utilization evaluation system. The evaluation system of the present invention covers multiple key aspects such as the physical phase composition, mechanical properties and shrinkage change of the shield slag sample, and can comprehensively and systematically evaluate the performance and practical potential of the shield slag in the resource utilization process, which helps to more accurately understand the actual application value of the shield slag and provide information basis for subsequent resource utilization decisions.

[0008] Optionally, the method for predicting resource utilization of shield slag further includes: analyzing the compressive strength damage rate under the dry-wet cycle test according to the resource utilization experimental information; constructing a dry-wet cycle shield slag compressive strength prediction model based on the compressive strength damage rate;

[0009] The compressive strength damage rate satisfies the following relationship:

[0010]

[0011] in, represents the damage coefficient of the unconfined compressive strength of shield soil under different drying and wetting cycles, represents the fluctuation index of experimental data, It represents the unconfined compressive strength of shield soil with a confidence level of 95% when there is no drying and wetting cycle. The present invention uses multi-dimensional evaluation results to analyze the compressive strength damage rate under dry-wet cycle test, and based on this, constructs a dry-wet cycle shield slag compressive strength prediction model, which can accurately evaluate the performance changes of the sample.

[0012] Optionally, the dry-wet cycle shield slag compressive strength prediction model satisfies the following relationship:

[0013]

[0014] in, It represents the unconfined compressive strength value of shield soil under dry-wet cycle with a confidence level of 95%. represents the damage coefficient of the unconfined compressive strength of shield soil under different drying and wetting cycles, It represents the maximum compressive stress when destroying shield soil. represents the average cross-sectional area of ​​shield muck, represents the statistical coefficient related to shield slag, The model of the present invention can accurately predict the compressive strength of shield slag under different dry-wet cycles, and the confidence level is set to 95% to further ensure the reliability of the data related to shield slag.

[0015] Optionally, the multi-dimensional evaluation result of resource utilization of shield slag samples obtained based on the shield slag resource utilization evaluation system and the resource utilization experimental information includes: establishing a moisture content linear shrinkage analysis function, a linear shrinkage analysis function, and a shrinkage coefficient analysis function of shield slag under different numbers of dry-wet cycles in the shield slag resource utilization evaluation system based on the resource utilization experimental information. The present invention establishes a moisture content linear shrinkage analysis function, a linear shrinkage analysis function, and a shrinkage coefficient analysis function, and the related functions can quantify the performance changes of shield slag under different numbers of dry-wet cycles, which is helpful for subsequent understanding of the performance characteristics of shield slag.

[0016] Optionally, the moisture content linear contraction analysis function satisfies the following relationship:

[0017]

[0018] in, It represents the linear shrinkage rate of moisture content of shield slag under different drying and wetting cycles. represents the density of shield soil after the nth dry-wet cycle, Table 2 shows the volume of shield soil after the nth dry-wet cycle. Indicates the initial mass of shield muck;

[0019] The linear shrinkage analysis function satisfies the following relationship:

[0020]

[0021] in, It represents the linear shrinkage of shield soil under different drying and wetting cycles. It represents the shield soil line shrinkage value after the nth dry-wet cycle. It indicates the initial linear shrinkage value of shield muck;

[0022] The shrinkage coefficient analysis function satisfies the following relationship:

[0023]

[0024] in, It represents the shrinkage coefficient of shield soil under different drying and wetting cycles. It represents the difference of shrinkage curve between the nth dry-wet cycle and the n-1th dry-wet cycle. express The corresponding difference in moisture content of shield slag.

[0025] The moisture content linear shrinkage analysis function of the present invention can accurately calculate the moisture content linear shrinkage of shield slag under different numbers of dry-wet cycles, thereby quantifying the relationship between its volume change and moisture content; the linear shrinkage analysis function can accurately reflect the linear shrinkage of shield slag after different dry-wet cycles, that is, the percentage change in length or size, which is helpful to evaluate its stability and durability; the shrinkage coefficient analysis function can calculate the ratio between the difference in shrinkage curves and the difference in moisture content, revealing the shrinkage characteristics of shield slag during the dry-wet cycle process.

[0026] Optionally, the multi-dimensional evaluation results of resource utilization of shield slag samples obtained based on the shield slag resource utilization evaluation system and the resource utilization experimental information include: extracting the physical phase composition information of shield slag based on the shield slag resource utilization evaluation system; obtaining the mechanical property prediction data of shield slag based on the dry-wet cycle shield slag compressive strength prediction model in the shield slag resource utilization evaluation system; obtaining the shrinkage change data of shield slag based on the moisture content linear shrinkage analysis function, linear shrinkage analysis function, and shrinkage coefficient analysis function in the shield slag resource utilization evaluation system; and obtaining the multi-dimensional evaluation results of resource utilization of shield slag samples by combining the physical phase composition information, the mechanical property prediction data, and the shrinkage change data. The multi-dimensional evaluation results of the present invention comprehensively consider multiple aspects such as the physical phase composition, mechanical properties, and shrinkage changes of shield slag, and can more comprehensively evaluate the resource utilization potential of different shield slags, help to more accurately understand the performance characteristics of different shield slags, and are conducive to the effective implementation of the prediction method for resource utilization of shield slag.

[0027] In the second aspect, in order to be able to efficiently execute the method for predicting resource utilization of shield slag provided by the present invention, the present invention also provides a system for predicting resource utilization of shield slag, the system comprising an input device, a processor, an output device and a memory, wherein the input device, the processor, the output device and the memory are interconnected, the memory comprises the method for predicting resource utilization of shield slag as described in the first aspect of the present invention, the memory is used to store a computer program, the computer program comprises program instructions, and the processor is configured to call the program instructions. The system for predicting resource utilization of shield slag provided by the present invention has a compact structure, strong applicability, and greatly improves the operating efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a flow chart of the method for predicting resource utilization of shield slag of the present invention;

[0029] Figure 2 It is a schematic diagram of the ray diffraction patterns of different shield slag samples in the method for predicting resource utilization of shield slag of the present invention;

[0030] Figure 3 It is a schematic diagram of the stress-strain curve of the shield slag sample under the dry-wet cycle in the method for predicting the resource utilization of shield slag of the present invention;

[0031] Figure 4 It is a schematic diagram of the relationship between the linear shrinkage rate of different shield slag samples and the number of dry-wet cycles in the method for predicting the resource utilization of shield slag of the present invention;

[0032] Figure 5It is a schematic diagram of the relationship between the shrinkage coefficient of different shield slag samples and the number of dry-wet cycles in the method for predicting the resource utilization of shield slag of the present invention;

[0033] Figure 6 This is a system structure diagram for predicting resource utilization of shield tunneling slag according to the present invention. DETAILED DESCRIPTION

[0034] The specific embodiments of the present invention will be described in detail below. It should be noted that the embodiments described herein are only for illustration and are not intended to limit the present invention. In the following description, a large number of specific details are set forth in order to provide a thorough understanding of the present invention. However, it is obvious to those of ordinary skill in the art that these specific details do not need to be adopted to implement the present invention. In other examples, in order to avoid confusing the present invention, known circuits, software or methods are not specifically described.

[0035] Throughout the specification, references to "one embodiment," "an embodiment," "an example," or "an example" mean that a particular feature, structure, or characteristic described in conjunction with the embodiment or example is included in at least one embodiment of the present invention. Therefore, the phrases "in one embodiment," "in an embodiment," "an example," or "an example" appearing in various places throughout the specification do not necessarily all refer to the same embodiment or example. In addition, particular features, structures, or characteristics may be combined in one or more embodiments or examples in any suitable combination and / or subcombination. In addition, it should be understood by those of ordinary skill in the art that the figures provided herein are for illustrative purposes and that the figures are not necessarily drawn to scale.

[0036] See also Figure 1 Based on the basic characteristics and properties of shield slag, the present invention constructs a comprehensive evaluation system for the resource utilization of slag, which can comprehensively and systematically analyze the performance and change laws of different shield slag in multiple aspects such as physical properties, mechanical properties and durability. Based on this, it is helpful to deeply explore the feasibility of different shield slag as resource utilization materials, lay a theoretical and practical foundation for resource utilization technology, and further promote the maximum utilization of resources and environmental sustainable development. The present invention provides a method for predicting the resource utilization of shield slag, and the method for predicting the resource utilization of shield slag includes the following steps:

[0037] S1. Select shield slag samples and formulate a shield slag resource prediction experiment plan based on the above shield slag samples. The specific setting steps and implementation contents are as follows:

[0038] Shield slag samples are selected based on the material characteristics of shield slag. In the embodiment, the shield slag samples include multiple groups of shield slag samples with different components; and a resource prediction experimental plan for shield slag is formulated based on the shield slag samples, wherein the resource prediction experimental plan mainly includes dry-wet cycle test and shield slag data detection, and the specific contents are as follows:

[0039] First, in this embodiment, slag samples from different shield tunnel construction projects were collected and selected. The above samples cover shield slag produced by different geological conditions, soil types and construction methods. In the preparation process of shield slag samples, each group of shield slag samples is processed according to unified and strict standards to ensure the uniformity and typicality of the obtained shield slag samples. At the same time, during the preparation process, it is necessary to control key parameters such as size, quality and shape of different shield slag samples to ensure consistency and comparability between the shield slag samples. The shield slag samples in the embodiment include multiple groups of shield slag samples with different components.

[0040] And according to the shield slag samples selected and set above, a resource prediction experimental plan for shield slag is formulated. In this embodiment, the resource prediction experimental plan mainly includes dry-wet cycle test and shield slag data detection, and the specific contents are as follows:

[0041] In this embodiment, the dry-wet cycle test refers to the dry-wet cycle test of the shield slag samples. The test is mainly divided into two parts: immersion saturation and drying dehydration. Based on this, the dry-wet alternation process of the shield slag in the actual environment can be simulated, which is beneficial to evaluate the changes in physical mechanics, chemical properties and other factors of different shield slag samples after experiencing different numbers of dry-wet cycles, and provide data support for analyzing the evolution of shield slag samples in strength, stability, shrinkage and other aspects.

[0042] The implementation steps of the dry-wet cycle test are as follows: During the sample preparation stage, the prepared shield slag samples are placed in a standard mold and cured for a specified time; during the dry-wet cycle operation stage, the shield slag samples are tested for multiple cycles according to the established dry-wet cycle process, including immersion saturation and drying and dehydration, and the sample status after each cycle is recorded. On the other hand, it is necessary to simultaneously record key data such as the mass, volume, and strength of the sample after each dry-wet cycle, which will help to analyze the relationship curve between the number of dry-wet cycles and the performance changes of the sample in the subsequent analysis, and reveal the changing laws of its different properties.

[0043] In this embodiment, the shield slag data detection is a comprehensive data monitoring process, which helps to fully understand the various properties of different shield slag samples and provide a scientific basis for the reuse and resource utilization of shield slag. Mainly through the existing data monitoring technology, the shield slag samples after the dry-wet cycle test are subjected to comprehensive data detection, including but not limited to chemical composition analysis monitoring, mechanical property data detection, permeability detection, radioactivity detection and physical data measurement.

[0044] Based on the above resource prediction experimental scheme, experimental information on resource utilization of shield slag samples can be obtained. Furthermore, the design content of the shield slag resource prediction experimental scheme in this embodiment is only an optional condition of the present invention. Other one or some embodiments can be optimized according to the actual conditions of the shield slag and the needs of the prediction experimental scheme. The composition and properties of the shield slag vary depending on various factors such as the construction site, geological conditions, and excavation technology. The experimental process is optimized according to the experimental needs, so that the present invention can adapt to the actual conditions of different shield slags to obtain more accurate and reliable experimental data.

[0045] S2. According to the resource prediction experimental scheme and shield slag sample set in step S1, experimental information on resource utilization of shield slag sample is obtained. The specific steps and implementation contents are as follows:

[0046] First, dry-wet cycle tests were carried out on the above-mentioned different shield slag samples to obtain shield slag samples after dry-wet cycle tests. The implementation contents are as follows:

[0047] Based on the above resource prediction experimental scheme, a dry-wet cycle test was carried out on the shield slag samples. The test mainly included two steps: immersion saturation and drying dehydration.

[0048] First, multiple groups of shield slag samples were placed into a cylindrical mold (or The shield slag samples were then cured in a curing box under standard conditions to obtain the slag samples for dry-wet cycles. In order to ensure the uniformity and comparability of the test results, the shield slag samples need to be dried in advance to a constant mass. In order to prevent the shield slag samples from disintegrating during immersion, two filter papers are used to wrap the cylinder up and down and fixed with rubber bands. At the same time, a permeable stone with a diameter of 8 cm is placed at the bottom of the specimen to ensure that the shield slag samples can absorb water evenly.

[0049] During the saturation stage, the wrapped shield slag samples and permeable stones were placed in a plastic water tank, and the interval between the samples was maintained. Then, water was slowly added to the water tank until the water filling height was 10 mm higher than the upper surface of the specimen. Next, the water tank was covered with a plastic cover to reduce water evaporation and avoid the influence of external factors on the sample saturation process. After soaking for 12 hours at room temperature of 26°C, the shield slag samples and permeable stones were taken out together, and after standing for 10 minutes, the flowing water in the tray was poured out for subsequent use.

[0050] In the drying and dehydration stage, the tray containing the saturated shield slag sample is placed in a blast drying oven. Considering that the national average daily maximum temperature is below 30°C, in order to speed up the dehydration process of the shield slag sample, the drying temperature of the drying oven is set to 30°C in this embodiment, and the shield slag sample is dried for 12 hours under this condition. Subsequently, the tray is taken out and cooled to room temperature, and the permeable stone and the shield slag sample are put into water again, thus completing a dry-wet cycle.

[0051] Furthermore, considering that cement, fly ash and WER have a significant impact on the strength and stability of shield slag samples, the shield slag samples after curing for 28 days were subjected to multiple dry-wet cycle tests in the embodiment, and the test times included 1 time, 3 times, 5 times, 10 times, 15 times and 20 times, and the relevant experimental results and information data were recorded.

[0052] Then, the shield slag data detection was carried out on the shield slag samples after the dry-wet cycle experiment to obtain the experimental information on the resource utilization of the shield slag samples. The detection contents are as follows:

[0053] The physical property test mainly focuses on the size, density, moisture content, particle size distribution, porosity and other information of the shield slag samples after wet cycle, so as to evaluate the impact of dry-wet cycle on the physical structure of shield slag. In this embodiment, physical size detection needs to focus on the size, shape and other characteristics of different shield slag samples. The shield slag can be analyzed for particle size by screening method or laser particle size analyzer to understand its particle distribution. The shape of the shield slag particles can be described and classified by microscopic observation or image analysis technology. Density detection can be measured by pycnometer method or drainage method, and accurate measurement can be performed using electronic balance, pycnometer, measuring cylinder and other equipment. Moisture content detection can be measured by drying method or other standard methods, and related ovens, electronic balances, dryers and other equipment can be configured. Particle size distribution detection can be detected by screening method or laser particle size analyzer, and standard sieves, vibrating screens, laser particle size analyzers and other equipment can be used accordingly. Porosity detection can be measured by volume method, water absorption method or pressure method, and accurate measurement can be performed using measuring cylinder, electronic balance, pressure device and other equipment.

[0054] Furthermore, when conducting the above-mentioned physical property tests, the accuracy and reliability of the relevant testing equipment and methods should be ensured. At the same time, the operating procedures should be strictly followed during the physical property test to ensure the accuracy and comparability of the test results. In addition, for shield slag samples of different sources and properties, different physical testing methods and equipment can be used to obtain more accurate and reliable test results.

[0055] Chemical property detection includes but is not limited to chemical composition analysis, pH detection, etc., in order to understand the changes in chemical composition and possible chemical reactions during the dry-wet cycle. In this embodiment, an X-ray diffraction test is used, which can be used to determine key information such as the crystal structure, phase composition, and lattice parameters of the shield slag sample. The shield slag sample can be microscopically tested by X-ray diffraction test technology to reveal the mineral composition and changes generated by the reaction of cement, fly ash, WER and other curing agents with the shield slag in different shield slag samples, and can also provide a basis for understanding the curing mechanism of shield slag and the optimization of curing formula.

[0056] The X-ray diffraction test in the embodiment utilizes the interaction between X-rays and electrons in matter. When X-rays are incident on different shield slag samples at a certain angle, they will be scattered by electrons in the crystal. The above-mentioned scattered waves are superimposed on each other inside the crystal to form a specific diffraction pattern. By measuring and analyzing the relevant diffraction patterns, the crystal structure, phase composition, lattice parameters and other information of the shield slag sample can be determined.

[0057] Furthermore, the diffractometer of this embodiment has the characteristics of high precision and high resolution, and can accurately measure and analyze the diffraction patterns of shield slag and related slag samples. By comparing the peak height and position of the standard diffraction card and the sample diffraction pattern, the relative intensity of the diffraction line can be estimated, and the standard card comparison can be carried out in combination with possible components such as slag, cement and fly ash, so as to determine the physical phase composition of different shield slag samples in the embodiment.

[0058] In an optional embodiment, the chemical property detection steps are as follows:

[0059] Samples were taken from different shield slag samples, crushed with a small hammer and soaked in anhydrous ethanol to terminate further reaction. Small pieces of soil from different samples were ground into powder using a grinder and sieved through a 200-mesh sieve. The sieved powder was placed in a roller furnace for Bake for 24 hours to remove moisture and volatile substances.

[0060] The powders of the above-mentioned different shield slag samples were placed in the sample slot of the X-ray diffractometer, and the instrument parameters were further adjusted to the predetermined values, including but not limited to the working voltage, current, scanning range and scanning speed. In the embodiment, a copper target was used as the X-ray source, the step size was 0.02°, the working voltage was 40kV, the current was 40mA, the scanning range was 5°-85°, and the scanning speed was .

[0061] It is necessary to collect and analyze relevant data simultaneously, that is, start the X-ray diffractometer to collect data, import the obtained diffraction pattern into the software for processing and analysis, and estimate the relative intensity of the diffraction line by comparing the peak height and position of the standard diffraction card and the diffraction pattern of the shield slag sample. In addition, the standard card comparison is carried out in combination with possible components such as slag, cement and fly ash to determine the physical phase composition of the shield slag sample.

[0062] By analyzing the test results of different shield slag samples, we can understand the mineral composition and its changes produced by cement, fly ash and WER and other curing agents after treating shield slag. For example, mineral components such as ettringite (AFt) and calcium hydroxide (CH) appeared in cement-cured samples; with the addition of fly ash, the diffraction peak intensity of quartz increased, and the diffraction peak intensity of calcium hydroxide (CH) gradually decreased; the addition of WER affected the diffraction peak intensity of cement-cured samples, but the overall peak shape remained similar. Based on this, it not only reveals the reaction mechanism between curing agents and different shield slag, but also provides a scientific basis for optimizing curing formulas and improving curing effects, which helps to understand the mineral composition and microstructure of different shield slag samples, thereby improving the mechanical properties and durability of shield slag samples.

[0063] In an optional embodiment, based on the above chemical property test results and X-ray diffraction pattern information, the diffraction data is imported into the relevant software through the diffractometer, and the main characteristic peaks of the shield slag sample are analyzed and identified by comparing with the standard diffraction card. For details, please refer to the X-ray diffraction test patterns of different shield slag samples. Figure 2 In the embodiment, five groups of experimental samples are set and the sample groups are numbered. The sample components are as follows: composite solidification sample-5, cement WER solidification sample-4, cement fly ash solidification sample-3, cement solidification sample-2, shield slag sample-1.

[0064] In an optional embodiment, Figure 2 The chemical composition and mineral composition of the first group of samples, namely the shield slag sample-1 experimental group, were fully and specifically analyzed. The composition information of the shield slag sample-1 can be found in Table 1.

[0065] Table 1 Information on chemical composition and mineral composition of shield slag sample 1

[0066]

[0067] Above Figure 2 The diffraction peaks of various minerals in the shield slag sample-1 are clearly displayed, which helps to further understand the mineral composition of the shield slag sample. Combining the chemical composition analysis and mineral composition analysis table, it can be found that the shield slag mainly contains , and The above components exist in minerals in the form of illite, kaolinite, vermiculite and montmorillonite. The content and proportion of minerals in shield slag sample-1 have an important influence on the physical properties and engineering application performance of shield slag.

[0068] Mechanical property testing is carried out on shield slag samples after dry-wet cycles, including but not limited to the slag properties, compressive strength, shear strength and other aspects of the shield slag samples, which will help to subsequently evaluate the mechanical stability and bearing capacity of its available resources.

[0069] Compressive strength is one of the important indicators for evaluating the mechanical stability of shield slag. Commonly used compressive strength testing methods include: unconfined compressive strength test, based on shield slag samples, axial pressure is applied without lateral constraints until the specimen is destroyed, and the maximum pressure at the time of destruction is recorded; triaxial compression test requires placing the shield slag sample in a triaxial pressure chamber, applying axial pressure and lateral pressure at the same time, and simulating different stress states by changing the size of the lateral pressure, so as to study the compressive strength of shield slag under different stress conditions.

[0070] Shear strength is a key indicator for evaluating the bearing capacity of shield slag. Commonly used shear strength testing methods include: direct shear test requires placing the shield slag sample in a shear box and applying horizontal shear force until the sample is sheared and damaged, while recording the shear force data at the time of damage; triaxial shear test requires applying shear forces of different directions and magnitudes to the shield slag sample in a triaxial pressure chamber to simulate the stress state of the shield slag sample in actual engineering, and by measuring the deformation and damage of the sample during the shear process, the shear resistance information and experimental data of the shield slag sample can be obtained.

[0071] According to the resource prediction experimental scheme designed in advance in step S1, and in combination with shield slag samples, a series of experiments on resource utilization are carried out, from which experimental data and information on resource utilization of shield slag samples are collected.

[0072] Furthermore, the method for obtaining experimental information on resource utilization of shield slag samples in this embodiment is only an optional condition of the present invention. In one or some other embodiments, the pertinence and practicality of the experimental plan can be improved based on the predicted target of the resource utilization method and the basic situation of the shield slag samples. Customizing the method for obtaining experimental information based on the predicted target and sample characteristics can more accurately capture the key information and potential value of the shield slag samples in the process of resource utilization, thereby providing a more scientific and reliable basis for subsequent resource utilization strategies.

[0073] S3. Based on the above resource utilization experimental information, a shield slag resource utilization evaluation system was established, and the multi-dimensional evaluation results of the resource utilization of shield slag samples were obtained based on the shield slag resource utilization evaluation system and resource utilization experimental information. The specific implementation contents are as follows:

[0074] Resource utilization evaluation indicators are set according to the resource utilization experiment information. In the embodiment, the resource utilization evaluation indicators mainly include the physical phase composition indicators, mechanical property indicators and shrinkage change indicators of the shield slag samples; based on the physical phase composition indicators, mechanical property indicators and shrinkage change indicators, the shield slag resource utilization evaluation system in this embodiment can be obtained.

[0075] In order to obtain accurate mechanical performance index information close to actual application conditions. In the embodiment, first, the compressive strength damage rate under the dry-wet cycle test is analyzed based on the above resource utilization experimental information; then, a dry-wet cycle shield slag compressive strength prediction model is constructed based on the compressive strength damage rate. The specific contents are as follows:

[0076] Based on the above-mentioned resource utilization experimental information and referring to the results of existing literature data, combined with the basic characteristics of different shield slag samples, in the existing stable material strength assessment method, the unconfined compressive strength is used as a key evaluation indicator. The existing method can calculate the unconfined compressive strength of solidified shield slag, and then accurately obtain the unconfined compressive strength value of solidified shield slag.

[0077] The above existing unconfined compressive strength calculation formula satisfies the following relationship:

[0078]

[0079] in, It represents the unconfined compressive strength of shield soil. It represents the maximum compressive stress that destroys the shield muck. represents the average cross-sectional area of ​​shield muck, represents the statistical coefficient related to shield slag, Represents the physical influence weight of shield debris.

[0080] In order to further ensure the accuracy and reliability of the calculation results of the unconfined compressive strength, this embodiment optimizes and improves the existing unconfined compressive strength calculation formula. The concept of confidence in statistics is introduced in the embodiment, and a 95% confidence level is selected to intercept the calculation results of the unconfined compressive strength. This means that under a large number of repeated test conditions, the obtained unconfined compressive strength value has a 95% probability of falling within the result range calculated in the embodiment, thereby greatly improving the reliability and confidence of the results, which not only helps to more accurately evaluate the mechanical properties of the material, but also provides a more solid theoretical basis and data support for subsequent engineering applications.

[0081] The above unconfined compressive strength calculation formula with a confidence level of 95% satisfies the following relationship:

[0082]

[0083] in, It represents the unconfined compressive strength value of shield slag with a confidence level of 95%. It represents the maximum compressive stress that destroys the shield muck. represents the average cross-sectional area of ​​shield muck, represents the statistical coefficient related to shield slag, Represents the physical influence weight of shield debris.

[0084] Based on the resource prediction experimental scheme of shield slag, it is now necessary to optimize the unconfined compressive strength model of shield slag samples under dry-wet cycle conditions. In the embodiment, different shield slag samples were subjected to different times of dry-wet cycle tests. According to the experimental information of resource utilization of shield slag samples, the change of unconfined compressive strength of shield slag under 1, 3, 5, 10, 15 and 20 dry-wet cycles can be obtained, and the strength damage rate of shield slag samples can be calculated accordingly. Based on this, we can have a deeper understanding of the dry-wet cycle effect, that is, the influence of the natural environment on the basic properties and related performance of shield slag.

[0085] In the embodiment, the compressive strength damage rate under the dry-wet cycle test is analyzed based on the resource utilization experimental information, wherein the damage calculation formula of the compressive strength under different dry-wet cycle times satisfies the following relationship:

[0086]

[0087] in, represents the damage coefficient of the unconfined compressive strength of shield soil under different drying and wetting cycles, represents the fluctuation index of experimental data, It represents the unconfined compressive strength of shield soil with a confidence level of 95% when there is no drying and wetting cycle. It represents the unconfined compressive strength of shield soil with a confidence level of 95% under n dry-wet cycles.

[0088] Based on this, we can further analyze the relationship between the number of dry-wet cycles and the damage coefficient of shield slag, as well as the relationship between the damage coefficient and the unconfined compressive strength. Based on the output results of the above damage calculation formula, a dry-wet cycle shield slag compressive strength prediction model was established, which can be used to describe the change law of the unconfined compressive strength of shield slag under different dry-wet cycles.

[0089] The above dry-wet cycle shield soil compressive strength prediction model satisfies the following relationship:

[0090]

[0091] in, It represents the unconfined compressive strength value of shield soil under dry-wet cycle with a confidence level of 95%. represents the damage coefficient of the unconfined compressive strength of shield soil under different drying and wetting cycles, It represents the maximum compressive stress when destroying shield soil. represents the average cross-sectional area of ​​shield muck, represents the statistical coefficient related to shield slag, Represents the physical influence weight of shield debris.

[0092] The statistical coefficients related to shield slag involve many aspects, including but not limited to the moisture content, density, particle distribution, strength characteristics, etc. of the slag. On the other hand, the statistical coefficients of shield slag also include a variety of influencing factors, such as geological conditions, construction technology, environmental conditions, etc. When establishing the dry-wet cycle shield slag compressive strength prediction model, the comprehensive influence of the above factors is fully considered to ensure the accuracy and reliability of the results.

[0093] The physical impact weight of shield slag refers to the relative importance or influence of the physical properties of shield slag, such as water content, density, particle distribution, strength, etc., on engineering construction, environment, and subsequent utilization during shield construction. In this embodiment, the physical impact weight of shield slag is determined by comprehensively considering multiple factors such as specific engineering background, geological conditions, construction requirements, and environmental protection standards.

[0094] At the same time, in order to quickly and accurately obtain the shrinkage change index information of the shield slag sample, the embodiment establishes the moisture content linear shrinkage analysis function, linear shrinkage analysis function and shrinkage coefficient analysis function of the shield slag under different dry-wet cycle times based on the above resource utilization experimental information.

[0095] When evaluating the shrinkage change performance of solidified shield slag samples, the embodiment mainly conducts a comprehensive analysis on three key shrinkage indicators: moisture content linear shrinkage, linear shrinkage rate and shrinkage coefficient. The specific values ​​of the above indicators can be calculated by moisture content linear shrinkage analysis function, linear shrinkage rate analysis function and shrinkage coefficient analysis function.

[0096] The above moisture content linear contraction analysis function satisfies the following relationship:

[0097]

[0098] in, It represents the linear shrinkage rate of moisture content of shield slag under different drying and wetting cycles. represents the density of shield soil after the nth dry-wet cycle, Table 2 shows the volume of shield soil after the nth dry-wet cycle. Indicates the initial mass of shield muck;

[0099] Moisture content refers to the water content inside shield slag, usually expressed as the percentage of water in the shield slag mass; linear shrinkage refers to the degree of reduction in length of shield slag during the drying process, usually expressed as the ratio of the difference between the dried length and the original length to the original length. The linear shrinkage is an important indicator for evaluating the shrinkage performance of materials and has an important influence on the dimensional stability and durability of the structure.

[0100] In the embodiment, the above two concepts are combined. The moisture content linear shrinkage rate refers to a quantitative indicator of the linear shrinkage degree of shield slag due to dry-wet cycles under a specific moisture content. Based on this, it can be used to describe the linear shrinkage degree of shield slag due to dry-wet cycles under specific moisture content conditions.

[0101] The density of shield soil after different wet-dry cycles refers to the mass or weight per unit volume of shield soil after multiple wet-dry cycles. The density of shield soil reflects the compactness, pore structure and material composition of the soil. During the wet-dry cycle, shield soil will go through two stages: wet and dry. In the wet stage, water is absorbed into the shield soil, causing its volume and mass to change. In the dry stage, water evaporates from the shield soil, resulting in a reduction in the volume and mass of the shield soil. The alternation of the above two stages will have a significant impact on the density of the soil.

[0102] In this embodiment, the initial density of the shield slag sample is set to , whose initial total volume is During the dry-wet cycle, the density of the slurry particles in the shield slag sample is fixed at , and will undergo changes in volume and record its volume at different times as .

[0103] As the dry-wet cycle proceeds, the total volume of the shield slag sample will change, which in turn affects the density of the shield slag sample. In order to quickly calculate the density of the shield slag under the action of the dry-wet cycle, the density change of the shield slag sample can also be analyzed more intuitively.

[0104] The density of shield soil after the above multiple dry-wet cycles satisfies the following relationship:

[0105]

[0106] in, represents the density of shield soil under the action of dry-wet cycle, represents the initial density of shield soil, represents the initial volume of shield muck, It represents the volume of soil particles in the shield slurry after the nth drying and wetting cycle.

[0107] Among them, the volume of soil particles in the shield slurry under multiple dry-wet cycles satisfies the following relationship:

[0108]

[0109] in, represents the volume of soil particles in the shield slurry under different drying and wetting cycles, represents the soil particle loss coefficient of shield slag, Indicates the number of dry-wet cycles, Indicates the proportion of soil particles in shield slag. represents the initial volume of shield muck, It represents the volume change of shield slag after the nth dry-wet cycle.

[0110] The initial mass of the shield slag sample satisfies the following relationship:

[0111]

[0112] in, represents the initial mass of shield muck, represents the initial density of shield soil, Represents the initial volume of shield muck.

[0113] The above linear shrinkage analysis function satisfies the following relationship:

[0114]

[0115] in, It represents the linear shrinkage of shield soil under different drying and wetting cycles. It represents the shield soil line shrinkage value after the nth dry-wet cycle. It indicates the initial linear shrinkage value of shield muck;

[0116] The linear shrinkage rate of shield soil under different numbers of drying and wetting cycles refers to the degree of reduction in the length of the shield soil sample after the alternating process of drying and wetting after experiencing different numbers of drying and wetting cycles. The above indicators are important parameters for measuring the shrinkage performance of shield soil, and are of great significance for evaluating the stability of soil during shield tunnel construction and operation.

[0117] Specifically, the linear shrinkage rate can be calculated by comparing the length change of the shield slag sample before and after drying. During the dry-wet cycle, the shield slag sample will go through two stages, wet and dry. The alternation of the above two stages will cause changes in the moisture and microstructure inside the shield slag sample, which will in turn affect the shrinkage performance of the soil. With the increase in the number of dry-wet cycles, the moisture in the shield slag will gradually reach a balance state, and the microstructure inside the soil will also undergo certain adjustments. The above changes will lead to changes in the linear shrinkage rate.

[0118] The linear shrinkage value of shield soil after dry-wet cycles refers to the absolute value of the linear shrinkage that occurs in the drying process of the shield soil sample after different dry-wet cycles. It can also be the difference between the length of the shield soil sample after drying and the original length. This difference directly reflects the degree of shrinkage of the shield soil under the action of dry-wet cycles and is an important indicator for evaluating the shrinkage performance of shield soil.

[0119] The above shrinkage coefficient analysis function satisfies the following relationship:

[0120]

[0121] in, It represents the shrinkage coefficient of shield soil under different drying and wetting cycles. It represents the difference of shrinkage curve between the nth dry-wet cycle and the n-1th dry-wet cycle. express The corresponding difference in moisture content of shield slag.

[0122] The shrinkage coefficient of shield slag under different numbers of dry-wet cycles refers to the degree of volume shrinkage of shield slag during the drying process after experiencing different numbers of dry-wet cycles. The shrinkage coefficient is a dimensionless parameter that reflects the volume change characteristics of shield slag during water loss. Specifically, the larger the shrinkage coefficient, the greater the shrinkage of shield slag during the drying process.

[0123] As the number of dry-wet cycles increases, the moisture in the shield slag will gradually reach a balance state, and the microstructure inside the soil will also undergo certain adjustments. The above changes will cause the shrinkage performance of the shield slag to gradually stabilize, and the change in the shrinkage coefficient will also tend to be gentle. However, in the initial stage, since the moisture and microstructure inside the soil have not yet reached a stable state, the shrinkage coefficient may fluctuate greatly.

[0124] Therefore, when evaluating the shrinkage performance of shield debris, it is necessary to fully consider the influence of the number of dry-wet cycles on the shrinkage coefficient. Analyzing the shrinkage coefficient of shield debris under different numbers of dry-wet cycles through experimental information will help to understand the change law of shrinkage performance of shield debris after multiple dry-wet cycles, which provides an important reference basis for the design and construction of shield tunnels.

[0125] In an optional embodiment, the physical phase composition information of shield slag is extracted based on the above-mentioned shield slag resource utilization evaluation system; the mechanical property prediction data of shield slag is obtained according to the dry-wet cycle shield slag compressive strength prediction model in the shield slag resource utilization evaluation system; the shrinkage change data of shield slag is obtained according to the moisture content linear shrinkage analysis function, linear shrinkage rate analysis function and shrinkage coefficient analysis function in the shield slag resource utilization evaluation system; and the multi-dimensional evaluation results of the resource utilization of shield slag samples are obtained by combining the physical phase composition information, mechanical property prediction data and shrinkage change data.

[0126] Firstly, the phase composition information of shield slag is extracted from the shield slag resource utilization evaluation system. The phase composition information can describe the mineral composition and chemical characteristics of different shield slag samples in detail.

[0127] Then, using the dry-wet cycle shield slag compressive strength prediction model in the evaluation system, the mechanical properties of shield slag can be predicted to obtain a series of data on its compressive strength. The above data provide information about the performance of the slag under stress and related information.

[0128] In addition, a comprehensive analysis of the shrinkage changes of shield slag was conducted through the moisture content linear shrinkage analysis function, linear shrinkage rate analysis function and shrinkage coefficient analysis function in the evaluation system. The relevant functions help to understand the volume changes of different shield slag samples under different moisture contents, as well as their shrinkage characteristics during the dry-wet cycle.

[0129] Finally, the above-mentioned phase composition information, mechanical property prediction data and shrinkage change data were combined to conduct a multi-dimensional evaluation of the resource utilization of shield slag samples. Not only the basic physical and chemical properties of the shield slag samples were taken into account, but also their stability and volume changes under stress conditions, thereby providing comprehensive and accurate information on the resource utilization of shield slag.

[0130] Furthermore, the relevant models and calculation functions for analyzing the multi-dimensional evaluation results of resource utilization in this embodiment are only an optional condition of the present invention. In one or some other embodiments, the analysis models and calculation functions of the multi-dimensional evaluation results can be flexibly selected and adjusted according to the resource utilization evaluation goals and the actual application requirements of shield waste. This not only helps to adapt to different resource utilization evaluation goals and the actual application requirements of shield waste, but also improves the accuracy and reliability of the evaluation system, and contributes to the specific implementation of the method for predicting the resource utilization of shield waste.

[0131] S4. Combined with the above-mentioned multi-dimensional evaluation results of resource utilization and the experimental information of resource utilization, a comprehensive prediction of the resource utilization degree of shield slag samples is made. The specific implementation contents are as follows:

[0132] In an optional embodiment, based on the above-mentioned multi-dimensional evaluation results of resource utilization, the stress-strain relationship of different shield slag under dry-wet cycles is analyzed. According to the compressive strength test results of shield slag samples under dry-wet cycles, representative shield slag sample data are selected, including but not limited to shield slag sample-1, cement solidified sample-2, cement fly ash solidified sample-3, cement WER solidified sample-4 and composite solidified sample-5. Then, as the dry-wet cycle test proceeds, relevant data at four different time points of 4 hours, 7 days, 14 days and 28 days are selected for the above-mentioned samples to analyze the stress-strain relationship of different shield slag samples under loading, and the above data are plotted into a curve graph. For details, please refer to Figure 3 , Figure 3 (a) shows the stress-strain relationship of the dry-wet cycle test time of 4 hours. Figure 3 (b) shows the stress-strain relationship of the dry-wet cycle test for 7 days. Figure 3 (c) shows the stress-strain relationship of the dry-wet cycle test for 14 days. Figure 3 (d) shows the stress-strain relationship after a dry-wet cycle test for 28 days.

[0133] based on Figure 3 From the multi-dimensional evaluation results of resource utilization and the experimental information of resource utilization, it can be seen that the shield slag samples continue to show significant ductility characteristics in mechanical properties. However, when cement, fly ash and WER are added, the shield slag samples show different degrees of brittle characteristics. Further observation Figure 3 It can be seen that compared with cement-solidified samples, cement-fly ash-solidified samples and cement-WER-solidified samples exhibit stronger elastic-plastic behavior.

[0134] As the dry-wet cycle test time continues to increase, the maximum stress peak of the sample shows a gradual upward trend. At the same time, the brittle characteristics of the cement-based solidified sample become more and more obvious; the failure mode of the composite solidified sample is also affected by the increase in time, gradually changing from plastic failure to brittle failure. However, the stress peak position of the cement solidified sample and the cement fly ash sample shifts toward the low strain direction, while the stress peak position of the composite solidified sample shows a trend of moving from 2.3% to the high strain direction.

[0135] based on Figure 3 Comparative analysis of different shield slag samples shows that WER has a more significant effect on the mechanical response of the solidified samples, especially in terms of elastic-plastic behavior. The solidified samples with WER added can show strain hardening characteristics under large deformation conditions. This characteristic not only increases the stress peak of the sample, but also effectively improves the original brittle failure mode of the cement solidified sample. Therefore, WER is particularly suitable for reinforcing shallow foundations, embankments on soft soil sediments, and other earthworks that may experience large deformations.

[0136] According to the changing trend of stress-strain curve, the stress-strain relationship of the solidified sample can be roughly divided into five stages. Figure 3 The following are clearly shown and labeled with letters A to E:

[0137] Section 0A (pore compaction stage): At the beginning of the test, as the pressure applied by the press gradually increased, the pores in the sample were further compacted. In this stage, the pore compression of the cement-based cured sample caused the slope of the stress-strain curve to gradually increase, and the curve showed an upward concave shape. At the same time, the compressive strength of the sample also gradually increased.

[0138] AB section (elastic stage): In this stage, there is an approximate linear relationship between stress and strain, indicating that the cement-based solidified shield slag begins to enter the hardening process. The linear change continues until point B, and the stress corresponding to this point is called the proportional limit. With the increase of curing age, the linear stage of the cement-based solidified specimens with the same proportion will be prolonged, and its compressive strength will also increase accordingly. The external load at this stage is mainly borne by the soil skeleton connected by hydration products, fly ash microbeads and WER matrix filling, and energy is absorbed through elastic deformation between the specimen materials.

[0139] BC section (elastic-plastic stage): When the external load exceeds 80%-90% of the ultimate load, the growth rate of the curve begins to slow down. In this stage, the stress-strain curve of the cement-based specimen has two forms: one is that when the curing time is short, the stress directly enters the nonlinear change stage after crossing the proportional limit until it reaches the peak point C; the other is that with the increase of the curing age, the stress crosses the proportional limit and then shows a short upward concave change before reaching the peak. The above stage is the period when the specimen mainly absorbs external energy, among which fly ash microspheres and WER bear greater plastic deformation.

[0140] CD section (softening stage): After the stress reaches the peak value, the bearing capacity of the specimen decreases significantly with the increase of strain.

[0141] DE section (residual strength stage): In this stage, the specimen still retains a certain strength after destruction. Although the tangent modulus at each point of the stress-strain curve is negative, due to the presence of the necked core, the specimen can still maintain a certain bearing capacity after destruction.

[0142] In an optional embodiment, based on the above-mentioned multi-dimensional evaluation results of resource utilization, the shrinkage changes of different shield wastes under dry-wet cycles are analyzed.

[0143] The linear shrinkage rate in the shield slag resource utilization evaluation system is an important indicator to measure the degree of longitudinal shrinkage deformation of the shield slag sample after experiencing dry-wet cycles. Its size is deeply affected by multiple factors such as the mineral composition, skeleton structure and initial water content of the shield slag sample. In order to deeply understand the specific effects of the above factors on the linear shrinkage rate, the shield slag samples were subjected to 1, 3, 5, 10, 15 and 20 dry-wet cycles respectively. The linear shrinkage rate data after each cycle are shown in Table 2.

[0144] Table 2 Statistical table of linear shrinkage information of shield slag samples under different drying and wetting cycles

[0145]

[0146] The relationship between the linear shrinkage and the number of dry-wet cycles of different shield slag samples was further analyzed, and a schematic diagram of the relationship between the linear shrinkage and the number of dry-wet cycles of shield slag sample-1, cement solidified sample-2, cement fly ash solidified sample-3, cement WER solidified sample-4 and composite solidified sample-5 was drawn. For details, please refer to Figure 4 .

[0147] The shrinkage coefficient in the shield slag resource utilization evaluation system, as a measure of the slope of the straight line segment on the shrinkage curve, directly reflects the longitudinal shrinkage rate experienced by the sample when it loses unit water content during the linear shrinkage stage. The above coefficient not only reveals the positive correlation between shrinkage deformation and water content change, that is, the more the water content decreases, the greater the shrinkage deformation; but also reflects the influence of the strength of the structural connection of the shield slag particles on its stability, where the weaker the structural connection means the smaller the interaction force between the particles, resulting in a larger shrinkage coefficient.

[0148] In addition, the shrinkage coefficient is different from the linear shrinkage rate. The linear shrinkage rate depends more on the initial moisture content of the sample, while the shrinkage coefficient focuses on the properties of the solidified shield slag itself and is not directly affected by the initial moisture content. Therefore, the shrinkage coefficient becomes a more pure indicator that can be used to evaluate the stability of the shield slag and its ability to resist shrinkage deformation. The smaller the shrinkage coefficient, the stronger the stability of the solidified shield slag, and its ability to resist shrinkage deformation is also correspondingly improved.

[0149] The shrinkage coefficients of different shield slag samples under different dry-wet cycle times in the examples are shown in Table 3.

[0150] Table 3 Statistical table of shrinkage coefficient of shield slag samples under different drying and wetting cycles

[0151]

[0152] In the embodiment, a curve diagram showing the relationship between the shrinkage coefficient of different shield slag samples and the number of dry-wet cycles is drawn. For details, please refer to Figure 5 .

[0153] according to Figure 5 The information can further explain and analyze the changing trend of the shrinkage coefficient of different shield slag samples and its relationship with the number of dry-wet cycles, as well as the performance differences between different shield slag samples.

[0154] First, the shrinkage coefficient of the shield slag sample shows a concave change trend of first decreasing and then increasing with the increase of the number of dry-wet cycles. Specifically, after 1 to 5 dry-wet cycles, the shrinkage coefficient of the sample gradually decreases, and the above law is consistent with the change law of shrinkage rate with the number of dry-wet cycles. However, when the number of dry-wet cycles exceeds 5 times, the shrinkage coefficients of different samples begin to show different trends, among which the shrinkage coefficients of cement-cured samples, cement-fly ash-cured samples and cement-WER-cured samples gradually increase, while the shrinkage coefficient of the composite-cured samples slowly increases after 6 to 10 dry-wet cycles. On the other hand, the growth rate of the shrinkage coefficient of the cement-WER-cured sample during 5 to 15 dry-wet cycles exceeds that of the cement-fly ash sample.

[0155] The change characteristics of the shrinkage coefficient of the composite curing sample reflect that it has better anti-wetting and anti-drying effect and higher water stability than the single curing material sample. In addition, with the increase of curing material dosage, the change range of the shrinkage coefficient of the composite curing agent gradually decreases, showing a more stable change trend.

[0156] In addition, it was observed that the water immersion behavior in the initial stage of the dry-wet cycle test had a certain promoting effect on the strength of the cured specimens. This may be because the water immersion cycle activated the hydration reaction of hydraulic binders such as cement, thereby promoting the rehydration process and thus improving the strength of the specimens.

[0157] In summary, there is a complex relationship between the shrinkage coefficient of different shield slag samples and the number of dry-wet cycles. The performance of different shield slag samples after dry-wet cycles is also different. The composite solidified sample is a solidified material worthy of promotion due to its excellent anti-dry-wet effect and stability. At the same time, the water immersion behavior in the early stage of the dry-wet cycle test also has certain practical significance for improving the strength of the solidified sample.

[0158] In this embodiment, the following steps are designed and implemented for shield tunneling slag samples to evaluate their resource utilization potential and predict their utilization degree.

[0159] First, representative shield slag samples are selected and a resource prediction experimental plan is formulated based on them. The plan should cover multiple links such as the collection, processing and analysis of shield slag samples to ensure the accuracy and reliability of the experimental results.

[0160] Then, according to the predetermined experimental plan, a series of resource utilization experiments were carried out on the shield slag samples. During the experiment, various experimental data were recorded and analyzed in detail to obtain preliminary information on the resource utilization of shield slag samples.

[0161] Then, based on the above experimental information, a shield slag resource utilization evaluation system was constructed. The above system can comprehensively consider multiple dimensions such as the physical properties, chemical composition, and environmental impact of shield slag samples to comprehensively evaluate their potential and value for resource utilization.

[0162] Based on the evaluation system and experimental information, a multi-dimensional evaluation of the resource utilization of shield slag samples was conducted. This step aims to deeply explore the resource utilization potential of shield slag samples and provide a scientific basis for their subsequent resource utilization.

[0163] Finally, combining the multi-dimensional evaluation results and experimental information, a comprehensive prediction is made on the resource utilization degree of shield slag samples. The prediction method for the resource utilization of shield slag of the present invention is based on the actual situation of shield slag samples, providing strong support for its future resource utilization, and conducting a comprehensive and in-depth evaluation of the resource utilization potential of shield slag samples, providing a strong scientific basis and decision-making support for its subsequent resource utilization.

[0164] See also Figure 6 In an optional embodiment, in order to efficiently execute a method for predicting resource utilization of shield slag provided by the present invention, the present invention also provides a system for predicting resource utilization of shield slag, wherein the system includes a processor, an input device, an output device and a memory, wherein the processor, the input device, the output device and the memory are interconnected, wherein the memory is used to store a computer program, wherein the computer program includes program instructions, and the processor is configured to call the program instructions to execute the method for predicting resource utilization of shield slag and the specific steps of the related embodiments provided by the present invention. The system for predicting resource utilization of shield slag of the present invention has a complete structure and is objectively stable.

[0165] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. These modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be included in the scope of the claims and specification of the present invention.

Claims

1. A method for predicting the resource utilization of shield slag, characterized in that: The method comprises: Selecting shield slag samples, and formulating a shield slag resource prediction experiment plan based on the shield slag samples; Obtaining resource utilization experimental information of the shield slag sample according to the resource prediction experimental plan and the shield slag sample; Establishing a shield slag resource utilization evaluation system based on the resource utilization experimental information, and obtaining a multi-dimensional evaluation result of resource utilization of shield slag samples according to the shield slag resource utilization evaluation system and the resource utilization experimental information; Combining the resource utilization multi-dimensional evaluation results and the resource utilization experimental information, a comprehensive prediction is made on the resource utilization degree of the shield slag sample; The shield slag resource utilization evaluation system established based on the resource utilization experimental information includes: Setting resource utilization evaluation indicators according to the resource utilization experimental information, wherein the resource utilization evaluation indicators include a physical phase composition indicator, a mechanical property indicator, and a shrinkage change indicator of the shield slag sample; The phase composition index, the mechanical property index and the shrinkage change index constitute a shield slag resource utilization evaluation system; The method for predicting resource utilization of shield slag also includes: Analyze the compressive strength damage rate under the dry-wet cycle test based on the resource utilization experimental information; Based on the compressive strength damage rate, a dry-wet cycle shield slag compressive strength prediction model is established; The compressive strength damage rate satisfies the following relationship: , in, represents the damage coefficient of the unconfined compressive strength of shield soil under different drying and wetting cycles, represents the fluctuation index of experimental data, It represents the unconfined compressive strength of shield soil with a confidence level of 95% when there is no drying and wetting cycle. It represents the unconfined compressive strength of shield soil with a confidence level of 95% under n dry-wet cycles; The dry-wet cycle shield slag compressive strength prediction model satisfies the following relationship: , in, It represents the unconfined compressive strength value of shield soil under dry-wet cycle with a confidence level of 95%. represents the damage coefficient of the unconfined compressive strength of shield soil under different drying and wetting cycles, It represents the maximum compressive stress when destroying shield soil. represents the average cross-sectional area of ​​shield muck, represents the statistical coefficient related to shield slag, Represents the physical influence weight of shield debris.

2. The method for predicting resource utilization of shield tunneling slag according to claim 1 is characterized in that: The method of selecting shield slag samples and formulating a shield slag resource prediction experimental plan based on the shield slag samples includes: Selecting shield slag samples based on the material characteristics of the shield slag, wherein the shield slag samples include multiple groups of shield slag samples with different components; A resource prediction experimental plan for shield slag is formulated based on the shield slag sample, and the resource prediction experimental plan includes dry-wet cycle testing and shield slag data detection.

3. The method for predicting resource utilization of shield tunneling slag according to claim 2 is characterized in that: The resource utilization experimental information of the shield slag sample obtained according to the resource prediction experimental plan and the shield slag sample includes: Performing the dry-wet cycle test on the shield slag soil sample to obtain the shield slag soil sample after the dry-wet cycle test; The shield slag data detection is carried out on the shield slag samples after the dry-wet cycle experiment to obtain the resource utilization experimental information of the shield slag samples.

4. The method for predicting resource utilization of shield tunneling slag according to claim 1 is characterized in that: The multi-dimensional evaluation results of resource utilization of shield slag samples obtained based on the shield slag resource utilization evaluation system and the resource utilization experimental information include: According to the resource utilization experimental information, a moisture content linear shrinkage analysis function, a linear shrinkage rate analysis function and a shrinkage coefficient analysis function of shield slag under different dry-wet cycle times are established in the shield slag resource utilization evaluation system.

5. The method for predicting resource utilization of shield slag according to claim 4 is characterized in that: The moisture content linear contraction analysis function satisfies the following relationship: , in, It represents the linear shrinkage rate of moisture content of shield slag under different drying and wetting cycles. represents the density of shield soil after the nth dry-wet cycle, Table 2 shows the volume of shield soil after the nth dry-wet cycle. Indicates the initial mass of shield muck; The linear shrinkage analysis function satisfies the following relationship: , in, It represents the linear shrinkage of shield soil under different drying and wetting cycles. It represents the shield soil line shrinkage value after the nth dry-wet cycle. It indicates the initial linear shrinkage value of shield muck; The shrinkage coefficient analysis function satisfies the following relationship: , in, It represents the shrinkage coefficient of shield soil under different drying and wetting cycles. It represents the difference of shrinkage curve between the nth dry-wet cycle and the n-1th dry-wet cycle. express The corresponding difference in moisture content of shield slag.

6. The method for predicting resource utilization of shield tunneling slag according to claim 5 is characterized in that: The multi-dimensional evaluation results of resource utilization of shield slag samples obtained based on the shield slag resource utilization evaluation system and the resource utilization experimental information include: Extracting the physical phase composition information of shield slag based on the shield slag resource utilization evaluation system; Obtaining mechanical property prediction data of shield slag according to the dry-wet cycle shield slag compressive strength prediction model in the shield slag resource utilization evaluation system; The shrinkage change data of shield slag is obtained according to the moisture content linear shrinkage analysis function, linear shrinkage rate analysis function and shrinkage coefficient analysis function in the shield slag resource utilization evaluation system; The multi-dimensional evaluation results of resource utilization of shield slag samples are obtained by combining the phase composition information, the mechanical property prediction data and the shrinkage change data.

7. A system for predicting resource utilization of shield tunneling waste, characterized in that: The system includes a processor, an input device, an output device and a memory, wherein the processor, the input device, the output device and the memory are interconnected, wherein the memory is used to store a computer program, the computer program includes program instructions, and the processor is configured to call the program instructions to execute the method for predicting the resource utilization of shield tunneling slag as described in any one of claims 1-6.